2021
DOI: 10.1108/ijsms-04-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Comparing young adult responses to rational and emotional sports product advertisements: the moderating role of product type and gender

Abstract: PurposeThe purpose of the study was to compare young adult responses to rational and emotional sports product advertisements. The moderating roles of product type and gender were also examined.Design/methodology/approachThe study utilized a 2 (advertising appeal: emotional vs rational) ×2 (gender: male vs female)×2 (sport product type: utilitarian vs hedonic) research design. Data were collected from 160 sport product users. The collected data were analyzed using three-way analysis of variance (ANOVA).Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Within the aggregated responses, ice hockey was the most popular sport type. However, European football (in Figure 1 and further in the text referred to as football) reached more responses in the TOP 1 category (67) compared to ice hockey (52). On the other hand, this phenomenon is aligned with the theoretical premises arguing that significant international success increases the sport's popularity.…”
Section: Aggregated Results Of the Questionnaire Survey On The Percei...mentioning
confidence: 58%
See 1 more Smart Citation
“…Within the aggregated responses, ice hockey was the most popular sport type. However, European football (in Figure 1 and further in the text referred to as football) reached more responses in the TOP 1 category (67) compared to ice hockey (52). On the other hand, this phenomenon is aligned with the theoretical premises arguing that significant international success increases the sport's popularity.…”
Section: Aggregated Results Of the Questionnaire Survey On The Percei...mentioning
confidence: 58%
“…This can be perceived in two directions. The first direction represents the marketing of an organization's sports product [50][51][52], represented by a match or another sports event, where customers are the spectators (either on-site or via broadcasting on television). This aspect is still connected to the first strong stakeholder group, represented by the genuine fans and other customers buying the sports product.…”
Section: The Sustainability Of Sports Organizations and Their Sustain...mentioning
confidence: 99%
“…Sun et al (2010) stated that males and females act differently due to social, biological, and behavioural reasons. Many studies have confirmed the moderating role of gender when it comes to purchasing intentions (Ghasemi Siani et al, 2021; Stokburger‐Sauer & Teichmann, 2013). Moreover, according to Lin et al (2019), males and females feel and act differently about product likeability while making a purchase decision.…”
Section: Resultsmentioning
confidence: 94%
“…However, consumers buy for numerous reasons. Preceding studies (Khandelwal et al, 2016;Bamberg et al, 2015;Chaturvedi et al, 2020) have defined that consumers could be affected by the cognitive-rational appeal and make rational decisions based on their reasoning abilities, whereas the aesthetic and hedonic motives would be influencing their personified experiences while consuming (Ghasemi Siani et al, 2021;. Further, there is enough evidence in the literature that modern-day consumers prefer and value pleasurable experiences associated with the products (Kim and Hall, 2020;Kumar and Yadav, 2021).…”
Section: Introductionmentioning
confidence: 99%